1995
DOI: 10.1039/c39950001277
|View full text |Cite
|
Sign up to set email alerts
|

Unique structural features in silver(I) dithioether complexes: the single-crystal structures of [Agn(PhSCH2CH2CH2SPh)2n](BF4)n·0.5nH2O and [Agn(MeSCH2CH2CH2SMe)n](BF4)n

Abstract: The X-ray structure of [Agn(PhSCH2CH&H2SPh)2,1"' shows an infinite array of tetrahedral Agl atoms coordinated via one S-donor of four distinct PhSCH2CH2CH2SPh ligands, whereas [Ag,(MeSCH2CH2CH2SMe),]n+ is a chain polymer involving trigonal (p2-S)2,S ligation with one S-donor bridging two adjacent Agl centres while the other S-donor of the dithioether ligand is non-bridging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…In addition, the design and synthesis of novel coordination architectures controlled by varying the reaction conditions (including temperature, [18,19] metal/ligand ratio, [20] pH, [21] solvents, [22] and counter anions [23,24] ) are of great interest in coordination chemistry and reactions. Appropriate control of the reaction conditions makes it possible to construct new materials with useful properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the design and synthesis of novel coordination architectures controlled by varying the reaction conditions (including temperature, [18,19] metal/ligand ratio, [20] pH, [21] solvents, [22] and counter anions [23,24] ) are of great interest in coordination chemistry and reactions. Appropriate control of the reaction conditions makes it possible to construct new materials with useful properties.…”
Section: Introductionmentioning
confidence: 99%
“…31 This, together with the structures previously identified by us for the bidentate group 16 ligand complexes of Ag(I) and Cu(I), 29 prompted us to investigate the coordination chemistry of the group 16 tripod ligands with Ag(I). The reaction of 2 molar equiv of L 3 (L 3 ) MeC(CH 2 SeMe) 3 , MeC(CH 2 -TeMe) 3 , or MeC(CH 2 TePh) 3 ) with Ag[CF 3 SO 3 ] gave white, light-sensitive powders after the reduction of the solvent in vacuo and the addition of diethyl ether.…”
mentioning
confidence: 96%
“…Recently, there has been much interest in the use of¯exible bridging ligands in the construction of supramolecular architectures (Blake et al, 1995;Bu et al, 2002;Jaya Prakash & Radhakrishnan, 2006;Li et al, 2003;Tong et al, 1999;Wu et al, 2006;Zhang et al, 2006), because such ligands encode more variable chemical information, such as conformational freedom. These studies have shown that the nature of the anions, the terminal groups and the spacer length of potentially bridging ligands play fundamental roles in determining the structural types of the ®nal assemblies.…”
Section: Commentmentioning
confidence: 99%